PENGARUH TINGKAT NAUNGAN BERBEDA TERHADAP PERTUMBUHAN ASOSIASI Pennisetum purpureum cv. Mott DAN Centrosema pubescens - Jawak, M. S.,; N. M. Witariadi.,; I W. Wirawan (Jurnal Peternakan Tropika, 2025)
Forage plants include this element for the development of ruminant livestockproduction, because a large amount of ruminant livestock feed comes from forage plants (grassand legumes). This study aims to determine the effect of shade levels on the growth ofPennisetum purpureum cv.Mott and Centrosema pubescens associations. This study wasconducted for 3 months, from September to November 2024 in Sading Village, MengwiDistrict, Badung Regency. The experimental design to be applied in this experiment is acompletely randomized design (CRD) divided into four treatments and seven replications, so itis divided into 28 experimental units. While the shade level treatment used is as follows: N0:0% shade (without paranet layer); N1: 20% shade (1 paranet layer); N2: 40% shade (2 paranetlayers); and N3: 60% shade (3 paranet layers). The observed variables are growth variables,namely plant height, number of leaves, total number of leaves, number of branches, number oftillers, total number of tillers and branches, and leaf chlorophyll. The results of the studyshowed the effect of shade level on the growth of the association of Pennisetum purpureumcv.Mott and Centrosema pubescens, can increase legume height, number of branches, grasschlorophyll and total number of leaves and reduce the number of grass tillers and the number oftillers and total branches but have not been able to develop the variables of grass height,number of grass leaves, number of legume leaves and legume chlorophyll. According to thefindings of the study, it can be stated that the growth of the association of Pennisetumpurpureum cv. Mott and Centrosema pubescens is influenced by the level of shade and a shadelevel of 20% provides the best growth ABSTRAK Tanaman pakan termasuk faktor penting bagi perkembangan hasil ternak ruminansia,sebab sejumlah besar pakan ternak ruminansia bersumber pada tanaman pakan ternak (rumputdserta leguminosa). Penelitian ini memiliki tujuan mengetahui pengaruh tingkat naunganterhadap pertumbuhan asosiasi Pennisetum purpureum cv.Mott serta Centrosema pubescens.Penelitian ini dilangsungkan sepanjang 3 bulan, sejak bulan September hingga November 2024di Desa Sading, Kecamatan Mengwi, Kabupaten Badung. Rancangan percobaan yang hendakditerapkan di peercobaan ini ialah rancangan acak lengkap (RAL) terbagi atas empat perlakuanserta ulangan sejumlah tujuh kali, maka terbagi atas 28 unit percobaan. Sedangkan perlakuantingkat naungan yang digunakan sebagai berikut: N0: Naungan 0% (tanpa lapis paranet); N1:Naungan 20% (1 lapis paranet); N2: Naungan 40% (2 lapis paranet); serta N3: Naungan 60% (3lapis paranet). Variabel yang diamati ialah variabel pertumbuhan merupakan tinggitanaman,jumlah daun, jumlah daun total, jumlah cabang jumlah anakan, total jumlah anakandan cabang, dan klorofil daun. Hasil penelitian menunjukkan pengaruh tingkat naunganterhadap pertumbuhan asosiasi Pennisetum purpureum cv.Mott dan Centrosema pubescens,dapat menambah tinggi legum, jumlah cabang, klorofil rumput dan jumlah daun total sertamenurunkan jumlah anakan rumput dan jumlah anakaan dan cabang total namun belum sanggumengembangkan variabel tinggi rumput, jumlah daun rumput, jumlah daun legum dan klorofillegum. Menurut temuan penelitian bisa dinyatakan jika pertumbuhan asosiasi Pennisetumpurpureum cv. Mott dan Centrosema pubescens dipengaruhi oleh tingkat naungan yang dantingkat naungan 20% memberikan pertumbuhan yang terbaik.